Read aloud anthology : Adventures in time and place : biographies, folk tales, tall tales, and fables, nonfiction selections, plays, poems, songs, stories - A division of the McGraw-Hill companies (New York, 1987)
For use with both My World and Here I Am. Contains sources, stories and songs, biographies, folk tales, tall tales, fables, non-fiction selections, plays & poems
Keywords: Child rearing,Children; Education